ANALISIS TENTANG IMPLEMENTASI PEMBELAJARAN PACELATHON BAHASA JAWA DAN IMPLIKASI PEDAGOGI BERDASARKAN PERSPEKTIVE JEAN PIAGET - Sri Suparti; Nurul Hidayati Zahro; Retno Megawati; Endang Fuziati; Bambang Sumarjoko (Smart Education, 2025)
Abstract: This study examines the implementation of the Pacelathon method in Javanese language learning, which proves to be relevant to Piaget's stages of cognitive development. The method is adapted to the cognitive stages of students—preoperational, concrete operational, and formal operational—to create an interactive and contextual learning environment. The results show that Pacelathon helps students understand and apply the Javanese language in everyday conversations as well as in broader cultural contexts. Adapting the method to the cognitive development stages enhances the effectiveness of regional language learning, while also enriching students' cultural experiences. The implications of this study are significant for educators in designing approaches that align with students' cognitive development, while strengthening their cultural identity in the era of globalization. Further research is recommended to explore the application of Piaget’s theory in the teaching of other regional languages and the development of technology-based learning methods. Keywords: Pacelathon Method; Javanese Language Learning; Piaget's Cognitive Development; Cultural Identity. Abstrak: Penelitian ini mengkaji implementasi metode Pacelathon dalam pembelajaran bahasa Jawa, yang terbukti relevan dengan tahapan perkembangan kognitif menurut Jean Piaget. Metode ini disesuaikan dengan tahap-tahap perkembangan kognitif siswa—praoperasional, operasional konkret, dan operasional formal—untuk menciptakan lingkungan belajar yang interaktif dan kontekstual. Hasilnya menunjukkan bahwa Pacelathon membantu siswa memahami dan mengaplikasikan bahasa Jawa dalam percakapan sehari-hari serta konteks budaya. Penyesuaian metode dengan tahap perkembangan kognitif meningkatkan efektivitas pembelajaran bahasa daerah, sekaligus memperkaya pengalaman budaya siswa. Implikasi penelitian ini penting bagi pendidik dalam merancang pendekatan yang sesuai dengan perkembangan kognitif siswa, serta memperkuat identitas budaya mereka di era globalisasi. Penelitian selanjutnya disarankan untuk mengeksplorasi penerapan teori Piaget dalam pembelajaran bahasa daerah lainnya serta pengembangan metode pembelajaran berbasis teknologi. Kata kunci: Metode Pacelathon; Pembelajaran Bahasa Jawa, Perkembangan Kognitif Piaget, Identitas Budaya